Reimagining Human Rights: Harnessing the Power of Law for Global Health and Sustainable Development Goals - Singh, Bhupinder (Serikat Pengajar Hak Asasi Manusia Indonesia, 2023)
The concept of human rights has long been an integral part of global discourse, championed as a fundamental pillar of social justice and equity. In recent decades, the intersection of human rights, global health, and sustainable development has emerged as a critical area of concern and opportunity. This research paper delves into the dynamic intersection of human rights, global health, and sustainable development, with a particular focus on Sustainable Development Goal 3 (SDG 3) - Good Health and Well-Being. In the context of our rapidly changing world, by applying a multidisciplinary research method, this paper explores the evolving landscape of human rights preservation and the challenges posed by emerging global governance issues. By examining the role of law in promoting and safeguarding human rights within the framework of SDG 3, it offers a comprehensive analysis of the evolving global governance challenge in the quest for a healthier and more sustainable world.